The anterior insula bidirectionally modulates cost‐benefit decision‐making on a rodent gambling task. (6th October 2017) - Daniel, M. L.; Cocker, P. J.; Lacoste, J.; Mar, A. C.; Houeto, J. L.; Belin‐Rauscent, A.; Belin, D.
Abstract: Deficits in cost‐benefit decision‐making, as assessed in the Iowa Gambling Task (IGT), are commonly observed in neuropsychiatric disorders such as addiction. There is considerable variation in the maximization of rewards on such tasks, both in the general population and in rodent models, suggesting individual differences in decision‐making may represent a key endophenotype for vulnerability to neuropsychiatric disorders. Increasing evidence suggests that the insular cortex, which is involved in interoception and emotional processes in humans, may be a key neural locus in the control of decision‐making processes. However, the extent to which the insula contributes to individual differences in cost‐benefit decision‐making remains unknown. Using male Sprague Dawley rats, we first assessed individual differences in the performance over the course of a single session on a rodent analogue of the IGT (rGT). Rats were matched for their ability to maximize reward and received bilateral excitotoxic or sham lesions of the anterior insula cortex (AIC). Animals were subsequently challenged on a second rGT session with altered contingencies. Finally, animals were also assessed for instrumental conditioning and reversal learning. AIC lesions produced bidirectional alterations on rGT performance; rats that had performed optimally prior to surgery subsequently showed impairments, and animals that had performed poorly showed improvements in comparison with sham‐operated controls. These bidirectional effects were not attributable to alterations in behavioural flexibility or in motivation. These data suggest that the recruitment of the AIC during decision‐making may be state‐dependent and help guide response selection towards subjectively favourable options. Abstract : Lesions to the anterior insular cortex (AIC) produced bidirectional alterations in decision‐making on a rodent analogue of the Iowa Gambling Task. Rats displaying optimal strategy prior to surgery were impaired following lesions to the AIC whereas similar lesions improved performance in rats that initially performed poorly. These data suggest that there are marked inter‐individual differences in the way the insula is recruited to guide response selection towards subjectively favourable options.